Pemanfaatan Teknologi Unmanned Aerial Vehicle (UAV) untuk Pemetaan Kadaster - Rohmat Junarto; Djurjani Djurjani; Fajar Buyung Permadi; Dony Ferdiansyah; Pandu Kuncoro Admaja; Ahmad Rasis Sholikin; Rahardian Rahmansani (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
Abstract: Geospatial data (on horizontal and vertical positions) play an important role in decision making.Regarding that, the issue of funds, diversity of areas, human resources, and non-updated data become great obstacles. This study aims to examine the technological capabilities of Unmanned Aerial Vehicles (UAVs) or Unmanned Aircraft in acquiring and updating geospatial data, evaluating and inspecting changes in the conversion of agricultural land and the environment, as well as describing orthophoto extraction opportunities in digital services based on multipurpose cadastre. This research used a model combination method (concurrent triangulation). Several alternative requirements were derived to design methods of mapping, processing and controlling the quality of application to the concept of Fit For Purpose Land Administration (FFP-LA), and layering with Geographic Information Systems (GIS). The final product of this system is effective to produce and update land base map, evaluate and inspect changes in the conversion of land functions as well as facilitate digital services. The availability of open source software efficiently extracts and combines terrestrial and photogrammetric mapping products in real time and has the opportunity to realize multipurpose cadastre. The involvement of local human resources is applied to ensure legal certainty in the land registration system as well as to improve and strengthen the management of agrarian resourcesAbstract: Geospatial data (on horizontal and vertical positions) play an important role in decision making.Regarding that, the issue of funds, diversity of areas, human resources, and non-updated data become great obstacles. This study aims to examine the technological capabilities of Unmanned Aerial Vehicles (UAVs) or Unmanned Aircraft in acquiring and updating geospatial data, evaluating and inspecting changes in the conversion of agricultural land and the environment, as well as describing orthophoto extraction opportunities in digital services based on multipurpose cadastre. This research used a model combination method (concurrent triangulation). Several alternative requirements were derived to design methods of mapping, processing and controlling the quality of application to the concept of Fit For Purpose Land Administration (FFP-LA), and layering with Geographic Information Systems (GIS). The final product of this system is effective to produce and update land base map, evaluate and inspect changes in the conversion of land functions as well as facilitate digital services. The availability of open source software efficiently extracts and combines terrestrial and photogrammetric mapping products in real time and has the opportunity to realize multipurpose cadastre. The involvement of local human resources is applied to ensure legal certainty in the land registration system as well as to improve and strengthen the management of agrarian resources